Performance of Green Mussel (Perna viridis) in Monoculture and Polyculture System Within Sea Bass (Lates calcarifer ) - Nuning Mahmudah Noor; Arum Dwi Astuti; Eko Efendi (AQUASAINS, 2016)
Green mussel (Perna viridis) is oyster has high potential to be developed. A huge market demand is an important factor to optimized green mussel cultivation, there are to system that could be applied for cultivation green mussel is polyculture and monoculture. The purposed of this study is to determined growth performance of green mussel which culture in monoculture and polyculture system. Green mussel is culture in floating cage bath of monoculture and polyculture system. In polyculture system green mussel placed within seabass (Lates calcarifer). Growth performance of green mussel determined by comparizing growth in wide and body lenght using T-test to analyzed factor that assigned to growth performance used principle component analysis (PCA) to environment factor such as Total Amonia Nitrogen (TAN), Total Organic Matters (TOM), Total Suspended Solid (TSS) and phytoplankton both in polycultured and monocultured system. The result of this research was shown that growth in this significant shown from third place where sample collected at 0-100 in depth The results showed that this significant growth was shown from the third place where the samples were collected at 0-100 in depth and the second place where the samples were collected at 100-150 in depth. This is caused by availability of feed source such as TOM and phytoplankton thy driven by sea current. The significant value shown by growth in wide of mussel shell at 100-150 cm in depth.